2018
DOI: 10.1038/s41598-018-35604-z
|View full text |Cite
|
Sign up to set email alerts
|

Advanced laser scanning for highly-efficient ablation and ultrafast surface structuring: experiment and model

Abstract: Ultra-short laser pulses are frequently used for material removal (ablation) in science, technology and medicine. However, the laser energy is often used inefficiently, thus, leading to low ablation rates. For the efficient ablation of a rectangular shaped cavity, the numerous process parameters such as scanning speed, distance between scanned lines, and spot size on the sample, have to be optimized. Therefore, finding the optimal set of process parameters is always a time-demanding and challenging task. Clear… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
51
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 120 publications
(64 citation statements)
references
References 80 publications
6
51
2
Order By: Relevance
“…In detail, the material removal in terms of one layer is presented and the discussed structures after laser machining pointing to clear growth regimes. The contour plot points to a saturation in terms of material removal rate at increasing fluence with adjacent layer depth z layer , where the slope of the iso-ablation depth lines decreases at about 10 ⋅ F th ≈ 0.65 J cm −2 in good agreement with proposed models in literature concerning efficient laser ablation [17,21]. At low feed rates and small distance between two pulses starting from moderate fluence of 0.3 J cm −2 , bumps due to heating and melting are formed, where the characteristic semispherical morphology with several 10 μm of size covers the surface [49].…”
Section: Microstructural Evolutionsupporting
confidence: 85%
See 2 more Smart Citations
“…In detail, the material removal in terms of one layer is presented and the discussed structures after laser machining pointing to clear growth regimes. The contour plot points to a saturation in terms of material removal rate at increasing fluence with adjacent layer depth z layer , where the slope of the iso-ablation depth lines decreases at about 10 ⋅ F th ≈ 0.65 J cm −2 in good agreement with proposed models in literature concerning efficient laser ablation [17,21]. At low feed rates and small distance between two pulses starting from moderate fluence of 0.3 J cm −2 , bumps due to heating and melting are formed, where the characteristic semispherical morphology with several 10 μm of size covers the surface [49].…”
Section: Microstructural Evolutionsupporting
confidence: 85%
“…The threshold fluence F th , defined by the power density where ablation starts for the multi-pulse regime, of stainless steel was determined for the used samples by considering the assumption for the ablation efficiency [17,21]. An optimal fluence F opt = e 2 F th follows from a logarithmic ablation law and using a Gauss intensity distribution with a beam waist w 0 the dependency of the applied peak fluence F 0 can be studied.…”
Section: Laser Ablation Strategymentioning
confidence: 99%
See 1 more Smart Citation
“…The results showed that the resolution increases with laser repetition, and it also increases as the scanning speed decreases. This could also be explained by laser fluence theory, which assumed that at low scanning speed a high number of pulses per spot were achieved because of high pulse overlap, while small laser spot size resulted in laser fluence high above the ablation threshold and large ablation depths .…”
Section: Resultsmentioning
confidence: 99%
“…Defined ablation conditions are a prerequisite for low roughness and efficient laser ablation [7]. In principle the fluence, laser repetition rate, and scan speed are interdependent [8] and no global optimum can be reached.…”
Section: Introductionmentioning
confidence: 99%